David Scott correspondence - Scott, David, active 1777.
ALS written by Scott to Gen. Edward Hand relating to a military expedition against Indians in Pennsylvania during the Revolution.
Continental Army officer and frontiersman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hand, Edward, -- 1744-1802 -- Correspondence; United States. -- Continental Army; Indians of North America -- Pennsylvania; Pennsylvania -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers; Frontiersmen